Catching Up with the Technological Frontier: Micro-level Evidence on Growth and Convergence - Iacovone, Leonardo (2012)
In this article, we study how firm heterogeneity influences productivity catching up using plant-level data from Mexico. The article addresses three issues: first, it evaluates the process of convergence towards the global versus the local technological frontier in a middle-income country such as Mexico. Second, it systematically evaluates the role of technological efforts in determining the speed of convergence towards each of these technological frontiers. Third, it assesses the role of openness and trade integration in determining the speed of convergence and presents a horse race between integration and technological effort in explaining the determinants of heterogeneity in influencing the process of convergence toward both the domestic and the global technological frontier. Our results suggest that building firm-level technological capabilities is important for catching up with the global frontier. A policy focused on trade alone will facilitate convergence towards the best technological practices available locally, but it will fall short of encouraging convergence with the global frontier.